Determination of mercury in aquatic systems by DGT device using thiol-modified carbon nanoparticle suspension as the liquid binding phase. (21st August 2017) - Wu, Tianxing; Wang, Guozhong; Zhang, Yunxia; Kong, Mingguang; Zhao, Huijun
Abstract : DGT device using SH-CNPs as the liquid binding phase and cellulose acetate membrane as the diffusive layer is demonstrated for determination of Hg 2+ in natural waters. Abstract : A diffusive gradients in thin films technique (DGT) device using thiol-modified carbon nanoparticle (SH-CNP) suspension as the liquid binding phase and cellulose acetate membrane as the diffusive layer was evaluated for determination of Hg 2+ in water. Laboratory DGT validation experiments gave linear mass uptake over time ( R 2 ≥ 0.99) for Hg 2+ in solutions of different concentrations. The effect of pH, ionic strength and potential interfering ions on Hg 2+ binding with DGT devices was investigated. The results showed that the gathering amount of SH-CNPs-DGT for Hg 2+ reached the maximum when the pH of solution was close to neutral and the ionic strength of solution and co-existing potential interfering ions such as Cd 2+, Cr 3+, Cu 2+ and Pb 2+ had no significant effect on gathering of SH-CNPs-DGT for Hg 2+ . Finally, validation of the SH-CNPs-DGT devices was undertaken for Hg 2+ in spiked local water systems (Dongpu Reservoir and Nanfei River). For in situ measurements in Nanfei River water, the average labile Hg concentrations were 0.091 ± 0.009, 0.053 ± 0.003, and 0.071 ± 0.006 μg L −1 for three, six and seven days, respectively, which were lower than the value obtained by using ICP-MS, as DGT only measures ionic mercury and labile mercury species but direct measurement measures total mercury including inert organic species and large colloids.